EFFETS OF DIFFERENT CAVITY DISINFECTANT PROCEDURES ON MICROTENSILE BOND STRENGTH OF PERMANENT TEETH - Arzu Durer; Burak Buldur; Ceren Ozturk; Fatih Öznurhan (Cumhuriyet University, 2015)
AbstractAim:The aim of this study was to compare the effects of different cavity disinfectants and KTP laser applied before/after acid-etching on microtensile bond strength of a composite resin to permanent teeth. The selection of the right cavity disinfectants may reduce the residual bacteria after cavity preparation.  Materials and Methods:Chlorhexidine (CHX), propolis(PRO), ozonated water(OW), gaseous ozone(OG) and KTP laser were used for this purpose. Twenty two third molar teeth were divided into two groups (n=12,n=10). In the first group, the cavity disinfectants were used before acid-etching (n=12) and in the second group, cavity disinfectants were used after acid-etching(n=10). One group received no pre-treatment and was set as control(CONT). After sample preparation, composite crowns were built up and sticks were obtained from these samples. The sticks were then stressed in tension until failure using a universal testing machine and the data were recorded. The sticks were analyzed under SEM. Results:The μTBS values of the disinfectants applied before acid-etching were KTP>CONT>OW>PRO>CHX>OG and the μTBS values when disinfectant solutions were applied after acid-etching were KTP>CONT>PRO>OW>CHX>OG, respectively.SEM analyses showed cohesive fractures in increased μTBS. Conclusion:The cavity disinfectants should be used before acid-etching and the results of this study revealed that KTP and OW might be safely used as cavity disinfectants.